Natural history and phenotypic variation of Metaphotina brevipennis (Sassure 1872) (Acontistidae, Mantodea) - Queiroga, Drielly da Silveira (2022)
Selective forces that shape the evolution of species vary between environments and taxa, being a key driver of biodiversity. Highly seasonal environments provide additional selective pressure by requiring taxa to cope with changes in environmental conditions. In such environments, it is common for species to exhibit some degree of plasticity, which might reflect changes in developmental time, behavior, and morphological changes, such as color variation. Praying mantises (Mantodea) are known for their strategies involving color in aggressive and protective behaviors. Like many insects, their development and other traits can be affected by changes in the environment, such as seasonality. The Cerrado is a savanna with a remarkable dry season (May to October), where plants and animals respond by altering a variety of life traits to deal with its seasonality. Thus, this thesis investigated how a species of Cerrado mantis, Metaphotina brevipennis responds to these temporal variations and uses its morphological attributes in favor of its survival. We analyzed several factors related to the life history of this species, such as development, phenology, behavior, reproduction, and the impact of natural enemies. We also analyzed how the variation in the color of individuals is distributed over the seasons, whether their color leads to behavioral differences in habitat choice, and whether it enhances their camouflage. Our results indicate that M. brevipennis is highly plastic in its strategies, and populations vary phenologically between locations and over time, showing high adaptation to Cerrado seasonality. By describing for the first time the natural history of a Cerrado mantis, we hope this study serves as inspiration for future ones, addressing questions about the regulation of this plasticity and the key mechanisms behind it.